Enhancing endothelial colony-forming cells for treating diabetic vascular complications: challenges and clinical prospects - Liu, Yaqiong; Lyons, Caomhán J.; Ayu, Christine; O’Brien, Timothy (Frontiers in Endocrinology, 2024)
Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia, leading to various vascular complications. Accumulating evidence indicates that endothelial colony forming cells (ECFCs) have attractive prospects for repairing and restoring blood vessels. Thus, ECFCs may be a novel therapeutic option for diabetic patients with vascular complications who require revascularization therapy. However, it has been reported that the function of ECFCs is impaired in DM, which poses challenges for the autologous transplantation of ECFCs. In this review, we summarize the molecular mechanisms that may be responsible for ECFC dysfunction and discuss potential strategies for improving the therapeutic efficacy of ECFCs derived from patients with DM. Finally, we discuss barriers to the use of ECFCs in human studies in light of the fact that there are no published reports using these cells in humans.